2005
DOI: 10.1590/s0074-02762005000700021
|View full text |Cite
|
Sign up to set email alerts
|

A new black fly isolate of Bacillus thuringiensis autoagglutinating strain highly toxic to Simulium pertinax (Kollar) (Diptera, Simuliidae) larvae

Abstract: Formulations containing the entomopathogenic Bacillus thuringiensis serovar israelensis strain Bacillus thuringiensis is a Gram-positive, spore-forming bacterium which produces a parasporal body during sporulation. The proteins contained in the parasporal crystal (delta-endotoxins) are specific insect gut toxins which have no significant effect on non-target organisms (Siegel 2001). The mode of action after ingestion involves solubilization of the protein in the alkaline conditions of the insect midgut, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(16 reference statements)
1
5
0
4
Order By: Relevance
“…Isolate ID-MD4, obtained from M. domestica, showed the same percentage mortality against C. quinquefasciatus as the reference strain IPS-82. Similar observations were reported by Cavados et al (2005), who reported that bioassays of a B. thuringiensis isolate obtained from the black fly Simulium pertinax, which had been captured in a field in southeastern Brazil, was not only effective against S. pertinax but also had comparable toxicity against the important disease vector Aedes aegypti as reference strain IPS-82 which is only effective against mosquitoes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Isolate ID-MD4, obtained from M. domestica, showed the same percentage mortality against C. quinquefasciatus as the reference strain IPS-82. Similar observations were reported by Cavados et al (2005), who reported that bioassays of a B. thuringiensis isolate obtained from the black fly Simulium pertinax, which had been captured in a field in southeastern Brazil, was not only effective against S. pertinax but also had comparable toxicity against the important disease vector Aedes aegypti as reference strain IPS-82 which is only effective against mosquitoes.…”
Section: Discussionsupporting
confidence: 86%
“…The search for new B. thuringiensis isolates and their characterisation has been carried out by several research groups in different countries (Dias et al, 1999;Uribe et al, 2003;Cavados et al, 2005;Jara et al, 2006), these isolates being important in the control of insects because they represent new alternatives in integrated pest management (IPM). The majority of natural B. thuringiensis isolates with insecticidal activity are effective against lepidoptera larva (Alves et al, 1998), with B. thuringiensis strains active against diptera or coleoptera being more difficult to isolate (Mohammedi et al, 2006;Armengol et al, 2007).…”
Section: Bioassaysmentioning
confidence: 99%
“…In the biological activity assays against Ae. aegypti larvae, the strains these groups demonstrated they can be more effective against insects vectors than the strain currently used in programs to control of Dipteran vectors (Cavados et al, 2005). Such proteins may represent new unknown cry genes, but analysis of the genes that encode this toxin is required to understand the function of each of these polypeptides in larvicidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The autoagglutinating B. thuringiensis strains (LFB-FIOCRUZ 969, 1038 and 1043) and the B. thuringiensis serovar israelensis IPS-82 (LFB-FIOCRUZ 584), were growth in a fermentation medium based on soy flour and inorganic salts (such as MgSO 4 , MnSO 4 , FeSO 4 , ZnSO 4 , CaCl 2 ) developed in the Laborató rio de Fisiologia Bacteriana, IOC-FIOCRUZ (Cavados et al, 2005).…”
Section: Preparation Of Active Bacterial Biomassmentioning
confidence: 99%
“…Bacillus thuringiensis israelensis Berliner (B.t.i.) tem sido utilizada como princípio ativo de bioinseticida por sua patogenicidade e especificidade sobre larvas de borrachudos (LACEy;LACEy, 1981;BECkEr et al, 1992;BrOwN et al, 1998;2000;rODriGUES;wANDErLi;JOSé, 1998;NAyAr et al,1999;ChUNG et al, 2001;FiLLiNGEr;kNOLS;BECkEr, 2003;POLLOm, 2003;CAVADOS et al, 2005).…”
Section: Introductionunclassified